Analysis Of Load Balance In 20 Kv Distribution Systems On Power Losses - Bambang Winardi; Karnoto Karnoto; Ajub Ajulian ZM (PT. Banjarese Pacific Indonesia, 2024)
Load balancing is one of the things that must be considered by reducing the value of voltage drops or power losses that occur in distribution channels. It is necessary to know the characteristics of the load in an area or area with a balanced supply so that each phase is burdened evenly. Calculating the voltage drop on the distribution network conductors, the voltage drop on the KBN09 Slawi feeder was calculated. What will be calculated here is from the line to the transformer furthest from the GI, namely from the three-phase 20 kV main line, single-phase branching. The results of power calculations from GI Kebasen Tegal show differences between R, S and T phases with three 20 kV phases in pre-balance and post-balance conditions. As written, the value for R wire is 82661.52 W, for S 52613 W, while for the T phase the value is 60127.06 W. Meanwhile, the calculation of power losses from GI Kebasen Tegal shows differences between the R, S and T phases with 1 phase voltage in the conditions before balance and after balanced. On the 3-phase line for the R wire, the power loss decreases from 34,198 W to 17,0425 W, for S it increases from 11,540 W to 19,077 W, while for the T phase the value remains 15,274 W.